In‐situ Polymerization Methods for Polymer‐based Solid‐State Lithium Batteries. Issue 12 (18th October 2022) - Sun, Mengjun; Zeng, Ziqi; Zhong, Wei; Han, Zhilong; Peng, Linfeng; Cheng, Shijie; Xie, Jia
Abstract: The in‐situ polymerization methods ( in‐situ methods) have led to huge advancement in the development of solid‐state batteries (SSBs) with intimate interfacial contacts and continuous pathways for the conduction of lithium ion. Though promising, they still face obstacles that hinder their practical application, such as poor interfacial stability between initiators and electrodes and scalability challenges. To date, most studies have been largely focused on the discovery of novel monomers/oligomers that can be in‐situ polymerized. Additionally, recent reviews have examined the progress of monomers/oligomers and advantages of in‐situ methods. Recognizing this, in this review, we seek to summarize in‐situ methods from the viewpoint of initiators. We provide realistic assessments of interfacial stability of initiators with electrodes, and analyze their challenges and perspectives for actual application. We hope to inspire deeper considerations on selection of initiators and offer guidance for in‐situ preparation of SSBs with high performances. Abstract : Making polyelectrolytes on site : In this review, not only the in‐situ polymerization methods are summarized according to the types of initiators but the advantages and disadvantages are discussed. Particularly, the chemical and electrochemical stability between initiators and electrodes are analyzed, which helps reasonably select in‐situ methods to prepare solid‐state batteries with excellent electrochemical performances.